(untitled) (Academic Journal of Internal Affairs, 2022)
“Without infocommunication, it is difficult to imagine our lives in the 21st century, as without the Internet we cannot always meet our physiological needs today, but the infrastructures that provide them can be subject to massive attacks. The current issues of cybersecurity and cyberwarfare were discussed at the Ludovika Free University by Brigadier General László Kovács, professor of the Faculty of Military Science and Military Officer Training and cyber defence observer of the Hungarian Defence Forces Command.” (URL1) The presentation raised fundamental issues, phenomena that endanger the security of the determining conditions that interweave our daily lives, which we should be as widely aware of as possible. The General began his presentation by asking whether we can imagine our lives with a half-hour power cut. The situation of not turning on the lights, not watching TV, not having a chilled soft drink when we get home. How many of us are capable of this? From the beginning to the end of the lecture, the audience listened to the General in silence and with rapt attention. We asked Brigadier General László Kovács about what cyberwarfare is, since when we can talk about it, and how important cyber security is in our everyday lives.